Gonzalo Rojas Particular Language - Pizarro-Cortes, M (UNIV SANTIAGO CHILE, INST ESTUDIOS AVANZADOS, 2020)
This article approaches the poetry of Gonzalo Rojas with the aim of entering the poet s workshop. It is maintained that, of the multiple original aspects of Gonzalo Rojas work, there are three axial characteristics in his poetic language, composed by precise and recurrent style features. These characteristics are: (1) the use of the verses as manifestations of breakage and not of syntactic unity, whose main resource is enjambement; (2) the abundance of neologisms produced according to the compositional norms of Spanish, and, finally (3) the formulation of a sort of metaphorical/symbolic vocabulary generated from the repetition of images. Although these features are not exclusive to Rojas work, since they are resources common to a wide range of poetic works, the twist that the poet gives them is. Moreover, their functioning as a whole enhances the originality of the author s disruptive poetic style.